Analysis of Factors Influencing Continuance Intention on CSR-based Digital Platforms - Ridho, Aisyah; Arief, N. Nurlaela (Research Horizon, 2025)
Digital platforms for social impact, such as corporate social responsibility initiatives, are increasingly used to engage specific communities, including women in Indonesia. This study examines which beliefs most strongly drive users’ continuance intention toward Sisternet, a corporate social responsibility based digital platform for Indonesian women, using an integrated TAM–TPB model. Quantitative data were collected through an online survey of 162 active users and analysed using Partial Least Squares Structural Equation Modeling. Additionally, short open-ended questions and app-store reviews were thematically reviewed to enrich interpretation. Accessibility strongly enhances perceived ease of use, usefulness, and relative advantage. Continuance intention is primarily influenced by perceived ease of use, relative advantage, subjective norm, and perceived behavioural control, while perceived usefulness and attitude have no direct effect; perceived risk is minimal. Limitations include cross-sectional, self-reported data from a single platform and non-probability sampling. Managers should prioritise frictionless access, emphasise unique platform value, leverage community influence, and facilitate user engagement. The study extends TAM–TPB to CSR-driven platforms, highlighting accessibility as a key antecedent and suggesting that usefulness and attitude may act indirectly in shaping continuance intention.